2007
DOI: 10.1021/jm070375w
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of Drug−Brain Tissue Binding and in Silico Prediction for Assessment of Central Nervous System Drug Delivery

Abstract: A high-throughput method for rapid screening of in vitro drug-brain homogenate binding is presented. The method is based on a straightforward sample pooling approach combining equilibrium dialysis with liquid chromatography mass spectrometry (LCMS). A strong correlation of fraction unbound in brain (fu) between single compound measurements and 25-pooled compounds (R2 = 0.906) was obtained for a selection of structurally diverse CNS compounds with a wide range of fractions unbound. Effects of brain homogenate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 34 publications
7
104
1
1
Order By: Relevance
“…For each radioligand, f p and f ND were predicted using the datasets shown in Figure 2. Even though there was inconsistent use of lipophilicity for estimation of f p and f ND between our study (which used Moriguchi logP) and the studies of Wan et al (23) and Mauer et al (24) (which used clogP), we observed positive correlations between predicted and clinical k 2 in the healthy and AD groups (R 2 5 0.81 and 0.85, respectively) (Fig. 3B).…”
Section: Predicted Permeability and Kcontrasting
confidence: 57%
See 2 more Smart Citations
“…For each radioligand, f p and f ND were predicted using the datasets shown in Figure 2. Even though there was inconsistent use of lipophilicity for estimation of f p and f ND between our study (which used Moriguchi logP) and the studies of Wan et al (23) and Mauer et al (24) (which used clogP), we observed positive correlations between predicted and clinical k 2 in the healthy and AD groups (R 2 5 0.81 and 0.85, respectively) (Fig. 3B).…”
Section: Predicted Permeability and Kcontrasting
confidence: 57%
“…f P and f ND were estimated from in vitro binding experiments using mouse brain and plasma and the in silico lipophilicity of 24 CNS drugs (e.g., risperidone, haloperidol, and fluvoxamine) reported by Wan et al (23) and Maurer et al (24). The datasets were obtained from references, and then the regression relationships for clogP versus f ND and f ND versus f P were determined.…”
Section: Prediction Of Clinical Suvr In Amyloid Pet Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also a fundamental assumption when the slice method is used to calculate C u,brainISF from measured total amounts in brain. Tissue partitioning is determined mainly by nonspecific membrane partitioning (Wan et al, 2007) and should not be saturable even at high concentrations. Given the importance of this assumption, an investigation of the linearity of V u,brain was merited.…”
Section: Discussionmentioning
confidence: 99%
“…D and V cell represent the dilution factor and the cell volume (0.8 ml ⅐ g brain Ϫ1 ), respectively. Equilibrium dialysis of brain homogenate was performed as described previously (Wan et al, 2007).…”
Section: Methodsmentioning
confidence: 99%